Implementasi Edukasi Keluarga dan Pemberian Rebusan Daun Seledri untuk Menurunkan Tekanan Darah pada Pasien Hipertensi - Mu’thiya Hasymah; Madyo Maryoto (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is a major public health concern with a high prevalence and a significant risk of complications if left uncontrolled. Effective management requires not only pharmacological treatment but also non-pharmacological approaches and active family involvement. One potential non-pharmacological therapy is the use of celery (Apium graveolens), which is believed to lower blood pressure. This study aimed to evaluate the effectiveness of family education combined with celery decoction administration in reducing blood pressure among patients with hypertension. A descriptive case study design was employed using a family nursing care approach over three home visits, each lasting 30–45 minutes. The intervention included health education on hypertension and a demonstration of how to prepare and administer celery decoction, which was consumed twice daily. Data were collected through interviews, observation, and blood pressure measurements. The results showed a reduction in blood pressure from 159/90 mmHg to 130/80 mmHg, along with a decrease in symptoms such as headaches and dizziness. In addition, there was an improvement in family knowledge, caregiving skills, and the ability to modify the home environment. In conclusion, family-based education combined with the administration of celery decoction appears to be effective in reducing blood pressure and enhancing the family’s role in managing hypertension.